Digital Nomad and Analysis of Regional Economic Resilience of Tourism Sector in Bali Province After Covid-19 Pandemic - Nurina Noviarini; Palupi Lindiasari Samputra (Publikasi Indonesia, 2024)
This study aims to analyze the impact of the pandemic on Bali's regional economic resilience and how the workcation trend brought by digital nomad tourists able to encourage tourism recovery in Bali. The research method used is descriptive-analytical, including examining documents and statements from experts that explained the response to the economic shocks that occurred in Bali Province. Data sources were obtained from tourism ministry performance reports, BPS data, news articles and accredited journals. The study revealed that the resistance phase is demonstrated by the disruption of the tourism sector when the COVID-19 pandemic broke out, causing economic Bali to decline. The reorientation phase is demonstrated by the ability of government and business actors to adjust and adapt from shocks. The workcation trend brought by digital nomads is suitable for application during the adaptation period. The recovery phase is demonstrated by the revival of tourism in Bali Province with an increase in the number of foreign tourists. One of them comes from digital nomad tourists who increase regional income. Based on analysis using the regional economic resilience model, Bali Province in 2023 will approach economically resilient status.